Digital Stethoscope to Examine Patients According to Technical Guidelines of Covid-19 - Muhammad Ilhamdi Rusydi; M. Farhan; Yoan Winata; Dhiny Yurichy Putri; Muhammad Dani Anwar; Daelita Berliana H. (Electrical Engineering Dept, Engineering Faculty, Universitas Andalas, 2021)
Health professionals have to use Personal Protective Equipment (PPE) that could cover the entire body to prevent the transmission of the SARS-CoV-2 virus while examining patients. The current stethoscope is not compatible with the need of health professionals. Therefore, this project aims to create a digital stethoscope that can fulfill the requirement of health professionals to examine patients according to health service guidance in Covid-19 era. Three main objectives in designing the stethoscope are to meet the needs of health professionals, easy and convenient to use. The designed stethoscope has an amplifier circuit with 100 gain and a bandpass filter with 20 Hz and 700 Hz for low and high cut-off frequencies. It is also able to calculate the heart rate and displays it on the stethoscope screen. The stethoscope has a record function that lets the users replay sound as much as they need for the analysis. This digital stethoscope has function tests, performance tests and user satisfaction tests. Seven health professionals who are well-experienced in handling Covid-19 patients auscultate and provide an assessment of the three objectives design. The test results showed that this stethoscope satisfies the health professional’s requirements to examine the patient, grade 4.69 of 5. Health professionals also give a perfect rating for the objective of being easy to use. This stethoscope is the right choice for examining patients according to health service guidance in the Covid-19 era.